Polycladia myrica-based delivery of selenium nanoparticles in combination with radiotherapy induces potent in vitro antiviral and in vivo anticancer activities against Ehrlich ascites tumor - Abo-Neima, Sahar E.; Ahmed, Abdelhamid A.; El-Sheekh, Mostafa; Makhlof, Mofida E. M. (Frontiers in Molecular Biosciences, 2023)
Polycladia SeNPs (PoSeNPS) with sizes ranging between 17.48 – 23.01nm and 0.46±0.07& 0.08±0.01 selenium mass and atom%, respectively, were synthesized in this work using Polycladia myrica aqueous extract and characterized using seven parameters, SEM, TEM, UV spectra, Zeta potential, EDX, X-ray diffraction, and FTIR, then examined for their anticancer potentiality in vitro with maximum inhibition 80.57%, 73% and IC50=14.86 µg/mL, 50mg/mL against HCT-116 and EAC cell lines respectively. Polycladia SeNPs in vivo alone and in combination with laser therapy of power 2mw showed a potent therapy effect against Ehrlich ascites carcinoma (EAC). It was concluded that Se-NPs have low toxicity, high effectiveness as a photothermal agent for cancer therapy, and show promising applications for future biomedical fields. The combined therapy shows a very high significant decrease in tumor volume, massive tumor cell necrosis, shrinking, and disappearance. It also shows improvement in liver TEM, histology, kidney function (urea and creatinine), and liver enzymes (ALT and AST).